The power of tobacco : discipline, power and knowledge : decision to grow a controversial crop - Khumalo, Caroline Claudia Mugadza (SLU/Dept. of Urban and Rural Development, 2011)
The Tobacco industry finds itself in a vulnerable position as various international bodies lobby to curb its growth and consumption due to health, environmental and social concerns. Using Foucault’s theories of discipline, power and knowledge alongside with symbolic interactionism I conduct a study of tobacco growers and how communication motivates them to grow tobacco, cut down or grow trees, use child labour and become contract growers. I analyse the ways in which common symbols are used to gain access to information and the ways in which the stakeholders use power and knowledge to motivate action. The study takes place in Zimbabwe and focuses on flue- cured tobacco growers. If the tobacco industry is in danger there is a need for them to take steps to diversify away from growing tobacco. I investigate if there have been any steps taken towards diversification and if not, what forces are at play that keep the grower strung to this crop. Furthermore the growth of tobacco has been associated with activities such as the use of child labour and deforestation so I take a look at how communication has an effect in preventing or encouraging such activities. Lastly this paper identifies and suggests ways in which stakeholders can be more effective in their communication with the tobacco growers through analysing communication that I perceive to be efficient and effective.